The relationship between non-executive directors and corporate performance. - Ho, Long Shiuan. (2008)
We partake a 9-year study of selected listed companies in Singapore and investigate whether a more significant presence of non-executive directors on the board correlates with stronger performance growth. The study did not reveal significant correlation between the proportion of non-executive directors and growth of performance variables.